Bullying victimisation in adolescence: prevalence and inequalities by gender, socioeconomic status and academic performance across 71 countries. (November 2021) - Hosozawa, Mariko; Bann, David; Fink, Elian; Elsden, Esme; Baba, Sachiko; Iso, Hiroyasu; Patalay, Praveetha
Abstract: Background: Bullying victimisation is of global importance due to its long-term negative consequences. We examined the prevalence of victimisation and its inequalities in 15-year-olds across 71 countries. Methods: Data were from the Programme for International Student Assessment (March-August 2018). Students reported frequencies of relational, physical, and verbal victimisation during the last 12 months, which were analysed separately and combined into a total score. Prevalence of frequent victimisation (> a few times a month) was estimated, followed by mean differences in total score by gender, wealth and academic performance quintiles in each country. Meta-analyses were used to examine country differences. Findings: Of 421, 437 students included, 113, 602 (30·4%) experienced frequent victimisation, yet this varied by country—from 9·3% (Korea) to 64·8% (Philippines). Verbal and relational victimisation were more frequent (21·4%, 20.9%, respectively) than physical victimisation (15·2%). On average, boys (vs girls +0·23SD, 95%CI: 0·22–0·24), students from the lowest wealth (vs highest +0·09SD, 0·08–0·10) and with lowest academic performance (vs highest +0·49SD, 0·48–0·50) had higher scores. However, there was substantial between-country heterogeneity in these associations (I 2 =85%–98%). Similar results were observed for subtypes of victimisation—except relational victimisation, where gender inequalities were smaller. Interpretation: Globally, bullying victimisation was high, although the size, predominant subtype and strength of associations with risk factors varied by country. The large cross-country differences observed require further replication and empirical explanation, and suggest the need to and the large scope for reducing bullying victimisation and its inequity in the future. Funding: Japan Foundation for Pediatric Research